Wars of the Realm: Rise of the Fallen - Book 2 - Black, Chuck (Colorado Springs, Colorado : Multnomah Books, 2015)
Validus, the only angel standing in the way of the demonic Fallen, has risen to a position of power and respect but is pushed beyond his abilities when he is assigned to protect one unbelieving man, Drew Carter, racing against time to discover why Drew is so important to humanity's survival.
Keywords: Adventure and adventurers -- Fiction; Good and evil -- Fiction; Angels -- Fiction; Christian life -- Fiction; Blind -- Fiction; People with disabilities -- Fiction; Single-parent families -- Fiction; Family life -- Fiction -- South Carolina; Adventure stories; Good and evil -- Juvenile fiction; Angels -- Juvenile fiction; Blind -- Juvenile fiction; People with disabilities -- Juvenile fiction; Single-parent families -- Juvenile fiction; Families -- Juvenile fiction -- South Carolina; JUVENILE FICTION / Religious / Christian / Action & Adventure; JUVENILE FICTION / Action & Adventure / General; JUVENILE FICTION / Religious / Christian / Fantasy; Christian fiction